Phytochemical profiling and FTIR analysis of aqueous extracts from three selected ethnomedicinal plants of North East India - Khakhalary, Seema; Narzari, Silistina (Current Botany, 2025)
Ethnomedicinal plants have played an important role in natural product research and drug discovery since antiquity. The current study used phytochemical screening and Fourier Transform Infrared Spectroscopy (FTIR) to analyze the leaves of three ethnomedicinal plants identified in Goalpara area of Assam. The investigation was carried out to characterize the crude extract and identify the functional groups in these plants. Phytochemical screening revealed the presence of many secondary plant metabolites in the examined plants, including alkaloids, glycosides, flavonoids, terpenoids, steroids, tannins and phenolic compounds. The FTIR spectroscopy study revealed the existence of several key functional groups. The presence of various functional groups such as C-I stretch, C=O stretch, C-H stretch, and C-N was confirmed by FT-IR analysis. As a result, the current study provides solid support and a foundation for using these plant species as herbal treatments for a variety of diseases. This study confirms that aqueous leaf extracts of Zanthoxylum oxyphyllum Edgew., Rotheca serrata (L.) Steane & Mabb., and Blumea lanceolaria (Roxb.) Druce contains numerous bioactive compounds, in addition to previously reported phytochemicals, which could be utilized in the development of plant-based drugs.